2020
DOI: 10.1039/c9bm01889a
|View full text |Cite
|
Sign up to set email alerts
|

Oral biofilm elimination by combining iron-based nanozymes and hydrogen peroxide-producing bacteria

Abstract: Combining nanozymes and bacteria to eliminate dental biofilms in a mixed-species model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 40 publications
0
31
0
Order By: Relevance
“… 35 37 Targeting EPS is a promising approach in biofilm control and recent studies have declared kinds of nanoparticles disrupting biofilm microenvironment, which allows disruption of the matrix. 38 40 Targeted therapy for dental caries is becoming more popular, 41 so a thorough understanding of the targeted EPS is a keystone. Structural features of polysaccharides like molecular weight may play an important role in various biological activities.…”
Section: Discussionmentioning
confidence: 99%
“… 35 37 Targeting EPS is a promising approach in biofilm control and recent studies have declared kinds of nanoparticles disrupting biofilm microenvironment, which allows disruption of the matrix. 38 40 Targeted therapy for dental caries is becoming more popular, 41 so a thorough understanding of the targeted EPS is a keystone. Structural features of polysaccharides like molecular weight may play an important role in various biological activities.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the Fe 3 O 4 nanoparticles with peroxidase-like activity enhanced oxidative cleavage of biofilm components in the presence of H 2 O 2 , which prevented biofilms formation and exterminated both planktonic bacteria and microbes residing within the biofilm [38]. In other interesting research, the combination of iron oxide or iron sulphide nanozymes and bacteria generating biogenic H 2 O 2 was used to eliminate oral biofilms [39]. Our results showed that the obtained Fe-and N-co-doped porous carbon materials possess similar, intriguing properties.…”
Section: Discussionmentioning
confidence: 99%
“…Impressively, the nFeS not only exhibited a broad spectrum to both Gram‐positive and Gram‐negative bacteria, [ 11 ] but also eliminated biofilm and intracellular bacteria. [ 12 ] Further studies revealed that the antibacterial activity was dependent on a ferroptosis‐like death in bacteria dominated by the released ferrous iron from nFeS under the condition without molecules that can chelate iron or resist oxidative damage. [ 13 ] Unfortunately, the antibacterial performance of nFeS dramatically decreased for bacteria like Escherichia coli or Staphylococcus aureus in nutrient‐rich media or physiological environment, making them equivocal for in vivo antibacterial therapy.…”
Section: Introductionmentioning
confidence: 99%